2006
DOI: 10.1111/j.0012-155x.2006.00493.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Research for Poverty Reduction in Marginal Areas of Rural Syria

Abstract: Agricultural research in marginal dry areas can contribute to reducing poverty through the development of technological, institutional and policy options for poor farmers. Such research should address diversified opportunities and development pathways. This article analyses the diversity of livelihood strategies of rural people living in the Khanasser Valley in northwestern Syria, an area that is typical of marginal drylands. It proposes an operational classification of households based on their different live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…With a low (210 mm year -1 ) and highly variable rainfall (coefficient of variation 0.31), the Khanasser Valley, located at the fringe of the steppe in northern Syria, is a typical example of such an area. Attempting to diversify their low-external input barley-sheep production systems and to save on household expenses (La Rovere et al 2006), some innovative local farmers established during the 1980 s olive orchards in the flat areas of this valley, which they irrigate a few times during the summer with groundwater (Tubeileh et al 2004b). During the late 1990s, farmers started to plant olives on degraded stony lands of the foot slopes of the hills bordering the valley, which were previously used for barley production (with frequent crop failures) or sheep grazing.…”
Section: Introductionmentioning
confidence: 99%
“…With a low (210 mm year -1 ) and highly variable rainfall (coefficient of variation 0.31), the Khanasser Valley, located at the fringe of the steppe in northern Syria, is a typical example of such an area. Attempting to diversify their low-external input barley-sheep production systems and to save on household expenses (La Rovere et al 2006), some innovative local farmers established during the 1980 s olive orchards in the flat areas of this valley, which they irrigate a few times during the summer with groundwater (Tubeileh et al 2004b). During the late 1990s, farmers started to plant olives on degraded stony lands of the foot slopes of the hills bordering the valley, which were previously used for barley production (with frequent crop failures) or sheep grazing.…”
Section: Introductionmentioning
confidence: 99%
“…Multiyear technology data were collected during household surveys (La Rovere et al, 2006), additional farm visits, discussions with key informants, and the participatory evaluation described in the participatory technology evaluation section. Data were collected for the 2001-2002 "bad" (dry year), 2002-2003 "good" (wet year) and 2003-2004 (average year) agricultural seasons.…”
Section: Data Sourcesmentioning
confidence: 99%
“…An ICARDA study published in 2005 revealed the diversity of livelihood strategies of rural people living in the Khanasser Valley (La Rovere and Rovere et al, 2006). La Rovere and AwHassan (2005) classify the households of the Khanasser Valley into three clusters: agriculturists, labourers and pastoralists.…”
Section: The Khanasser Valley Integrated Research Site (Kvirs)mentioning
confidence: 99%
“…In Shallalah Saghirah, each extended household has individuals that fall under one of the three categories with a majority of labourers and pastoralists/sheepowners. AwHassan and La Rovere conclude that while agriculturists benefit most, poor labourers with enough land can also gain from pro-poor agricultural research La Rovere et al, 2006). However, the poorest households, the landless and pastoralists, do not gain much benefit.…”
Section: The Khanasser Valley Integrated Research Site (Kvirs)mentioning
confidence: 99%
See 1 more Smart Citation